Faktor-Faktor yang Mempengaruhi Produksi Kacang Tanah di Desa Fafinesu Kecamatan Insana Fafinesu Kabupaten Timor Tengah Utara - Maria Yosepha Fonisasi; Adeline Norawati Hutapea (AGRIMOR, 2019)
This study aims: 1. To find out the description of peanut farming in Fafinesu Village, Insana Fafinesu District; 2. To find out the factors that affect peanut farming in Fafinesu Village, Insana District, Fafinesu. The research was conducted from July to October 2018. The sampling technique was carried out using saturated / census sampling techniques. The sample used in this study was 63 respondents. Data analysis methods in this study include: qualitative descriptive methods and Cobb-Douglass analysis. The stages of peanut farming conducted in Fafinesu Village include: Land preparation, seed preparation, weeding and land processing, planting, maintenance, harvesting and post-harvest. Inputs used are: land area, seeds, labor, education and farming experience. The results of the study stated that peanut farming in Fafinesu Village uses intercropping cropping patterns. Peanut production is influenced by 3 factors, namely land area, seeds and labor while factors that do not significantly affect peanut farming production are education and experience in farming.